An in-depth examination of family child care providers and their engagement with outside systems using a mixed methods case study approach. (April 2021) - Hooper, Alison; Hallam, Rena
Highlights: A multiple case study approach was used to study family child care providers. Participants in different profiles varied in their perspectives on outside systems. Results can help ensure outside systems support family child care providers. Abstract: This study extends a previously identified and validated typology of home-based child care providers which used providers' reports of their beliefs and practices related to caregiving to categorize providers rather than regulatory status. We use a mixed methods case study approach to present findings from 12 licensed family child care providers with a specific focus on exploring differences in perspectives and engagement with outside systems among providers in different profiles. Data come from multiple sources, including state administrative data, provider surveys, an observational measure of program quality, interviews, and field notes. Findings highlight some consistent differences in practices, perspective, and engagement with systems between profiles. The case studies presented highlight and extend what is known about family child care providers' perspectives on quality improvement initiatives and how their perspectives relate to their practices with children and families. Results can inform the development and refinement of quality improvement initiatives offered to home-based child care providers.